Management of bacterial blight in rice (Oryza sativa) through combined application of endophytes and rhizosphere antagonist - SAIKIA, KAKUMONI; BORA, L C; BORA, POPY; HAZARIKA, HRISHIKESH (The Indian Journal of Agricultural Sciences, 2021)
Biocontrol agents and plant growth promoting microbes have emerged as an effective alternative for chemical management of plant diseases in addition to realising an increase the crop yield. Present study was made to explore endophytic microbes and rhizospheric Streptomyces of rice plant to develop biocontrol strategy for the management of bacterial blight (BB) of rice (Oryza sativa L.) caused by Xanthomonas oryzae pv. oryzae (Xoo). In-vitro studies revealed that few promising endophytic microbes (E1 and E2) and rhizospheric Streptomyces (S1 and S2) could suppress Xoo effectively in dual culture assay in- vitro. The combination of antagonistic microbes (E1+S1+S2) showed highest (58.71%) inhibition of BB pathogen. Pot experiments were conducted to study the effect of the promising endophytic microbes on disease reduction, yield and yield attributing characteristics of rice. Results revealed the lowest disease incidence in plants treated with combination of E1+S1+S2(10.29 %) compared to other treatments. Similarly, the highest yield (50.06g per hill) and other yield attributing characters of rice plants were recorded with microbial treatment E1+S1+S2. These observations suggested far better superiority of rhizosphere antagonists plus endophytes than either of the two alone.